Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A) \(100+\left(-3\right).\left(-5\right)-\left(-2\right)=100+\left(\left(-3\right).\left(-5\right)\right)+2=100+15+2=117\)
B) \(-2-4-6-8-10-12-14=\left(-2-4\right)+\left(-6-14\right)+\left(-8-12\right)+\left(-10\right)\)
\(=-6+\left(-20\right)+\left(-20\right)+\left(-10\right)=-6-20-20-10=-56\)
B = ( 2 - 4 - 6 + 8 ) + ( 10 - 12 - 14 + 16 ) +......+ ( 98 - 100 - 102 + 104 )
B = 0 + 0 +....+ 0 ( 52 số 0 )
B = 0
A=1+(3-5)+(7-9)+...+(2015-2017)
A=1+(-2)+(-2)+...+(-2)
A=(-2)*1008+1
A=(-2014)+1
A=-2015
Lời giải:
$A=1.1+2.2+3.3+...+100.100$
$=1(2-1)+2(3-1)+3(4-1)+...+100(101-1)$
$=1.2+2.3+3.4+....+100.101-(1+2+3+...+100)$
Có:
$X=1.2+2.3+3.4+....+100.101$
$3X=1.2(3-0)+2.3(4-1)+3.4(5-2)+....+100.101(102-99)$
$=3X=(1.2.3+2.3.4+3.4.5+....+100.101.102)-(0.1.2+1.2.3+...+99.100.101)$
$=100.101.102$
$\Rightarrow X=\frac{100.101.102}{3}$
$Y=1+2+3+...+100=100(100+1):2=5050$
$A=X-Y=\frac{100.101.102}{3}-5050=338350$